2021
DOI: 10.1039/d1ce00019e
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible MOF-808 as an iodophor antimicrobial agent with controlled and sustained release of iodine

Abstract: In recent years, an increasing occurrence of microbial resistance to biocidal materials has become a serious problem. In contrast with other biocides, iodine seems to have no real resistance issue,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Of note is the recent report of the use of MOFs has a carrier of iodine for medical and microbial applications. 164 ZIF-8 has been immobilised on titanium and can actas a carrier and release agent of iodine for antibacterial therapy in orthopaedics, the release of iodine being triggered by near ir radiation. 165 Likewise, the photochemical release of dichromate by iodine sorption in a water stable system 166 reflects the huge potential that MOFs have in developing new polyfunctional and targeted technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Of note is the recent report of the use of MOFs has a carrier of iodine for medical and microbial applications. 164 ZIF-8 has been immobilised on titanium and can actas a carrier and release agent of iodine for antibacterial therapy in orthopaedics, the release of iodine being triggered by near ir radiation. 165 Likewise, the photochemical release of dichromate by iodine sorption in a water stable system 166 reflects the huge potential that MOFs have in developing new polyfunctional and targeted technologies.…”
Section: Discussionmentioning
confidence: 99%
“… 62 Davoodi and co-workers have used MOF-808 as an iodophore antimicrobial agent, reporting a 19 mm zone of inhibition against Staphylococcus aureus with controlled and sustained release of iodine from iodine-loaded MOF-808. 64 In this study, we have shown MOF-808 can act as a cancer-targeted dual drug delivery system by combining FUDR and CARB in MOF structure for a synergistic combination therapy and by decorating MOF-808 with a glycopolymer for targeting cancer cells.…”
Section: Resultsmentioning
confidence: 85%
“…The terminal anions of monotopic ligands on the remaining sites of the eight-coordinated Zr­(IV) centers exhibit relative lability, allowing for postsynthetic modification (PSM) with therapeutics and targeted functional groups. Despite these advantages, MOF-808 has rarely been used as a drug delivery system compared to the much more widely studied Zr MOF UiO-66, potentially due to the fact that MOF-808 has been identified as an excellent catalyst for peptide hydrolysis. , Nevertheless, Zhang and co-workers have shown an efficient pH-dependent drug delivery of 5-FU toward HeLa cervical adenocarcinoma cells using folate-targeted MOF-808 with no apparent in vitro cytotoxicity of the MOF itself . Davoodi and co-workers have used MOF-808 as an iodophore antimicrobial agent, reporting a 19 mm zone of inhibition against Staphylococcus aureus with controlled and sustained release of iodine from iodine-loaded MOF-808 . In this study, we have shown MOF-808 can act as a cancer-targeted dual drug delivery system by combining FUDR and CARB in MOF structure for a synergistic combination therapy and by decorating MOF-808 with a glycopolymer for targeting cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…The proper combination of metallic nodes or clusters with organic ligands allows designing a broad range of MOFs. MOFs have attracted unparalleled attention due to their various applications in the synthesis of nanomaterials, gas storage, catalysis, antibacterial activity, biological sensing, and removal of hazardous contaminants. In particular, because of their unique and desirable features such as high pore volumes and acceptable pore diameters, high drug loading capacity, good biodegradability, and good biocompatibility, MOFs have recently been extensively explored as drug carriers. MOFs have the potential to increase drug solubility, enhance the antitumor effect, prolong the drug release time, change the pharmacokinetics of drugs, , and reduce side effects by lowering the dosage . Furthermore, controllable designing and the possibility to synthesize nanoscaled MOF nanoparticles make these nanomaterials ideal DDSs .…”
Section: Introductionmentioning
confidence: 99%